Trend analysis in management of juvenile nasopheryngeal angiofibroma: our institutional experience - Vasani, Heli H.; Joshi, Chinmayee P.; Patel, Kalpesh B. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Juvenile nasopharyngeal angiofibroma is a vascular malformation rather than true neoplasm. It accounts for 0.5% of all head and neck tumors and its general incidence is 1:150,000. It is uncommon, benign, extremely vascular tumor that arises from tissues in the sphenopalatine foramen, the pterygoid base causing Early spread submucosally towards nasopharynx. Surgical excision is mainstay of treatment. Methods: This is a retrospective observational study carried out from March 2002 to March 2019, 130 patients underwent surgical resection of juvenile nasopharyngeal angiofibroma at Civil Hospital, Ahmedabad. Patients were divided in two groups with Group-A having patients from 2002-2010 and Group B having patients from 2011-2019. Results: A total 130 cases of juvenile nasopharyngeal angiofibroma with a mean age of 16.25 years (range 9-33) were treated by surgical excision from March 2002 to March 2019. In Group A patients open approach was used most often with endoscopic approach used only till stage II-A. In Group B patients the preferred surgical approach was trans-nasal endoscopic approach cases up to stage IV-A and open approach including the midfacial degloving approach and infratemporal approach was used cases with extensive intracranial, lateral infratemporal fossa, orbit, optic nerve, cavernous sinus involvement. Conclusions: Our study shows that over the years there has been shift in surgical approaches used in treating angiofibroma with the advent of newer endoscopic method and addition of various technology such as coblation, navigation has made the procedure for a highly vascular tumor simpler.